The accidental systems librarian [electronic resource] - Engard, Nicole C., 1979-
This new edition of The Accidental Systems Librarian prepares readers to manage the latest library technologies : mobile devices, open source software, social networks, WiFi, ebooks, and much more. Nicole C. Engard's advice on using research, communication, organizational, and bibliographic skills to solve various systems problems is geared to helping both "accidental" and "planned" systems librarians develop the skills they need to succeed and the confidence they need to excel